2015
DOI: 10.2147/rrb.s61495
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sparks in the heart: dynamics and regulation

Abstract: Calcium (Ca2+) plays a central role in the contraction of the heart. It is the bi-directional link between electrical excitation of the heart and contraction. Electrical excitation initiates Ca2+influx across the sarcolemma and T-tubular membrane that triggered calcium release from the sarcoplasmic reticulum. Ca2+sparks are the elementary events of calcium release from the sarcoplasmic reticulum. Therefore, understanding the dynamics of Ca2+sparks is essential for understanding the function of the heart. To th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 104 publications
(119 reference statements)
0
13
1
Order By: Relevance
“…With time, sparks frequency raised two- to threefold, and the areas occupied with high frequency sparks substantially enlarged ( Figure 1 A, t = 60–63 s and t = 85–88 s). It is believed that Ca 2+ -sparks may underlie both the initiation and propagation of slow Ca 2+ -waves [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With time, sparks frequency raised two- to threefold, and the areas occupied with high frequency sparks substantially enlarged ( Figure 1 A, t = 60–63 s and t = 85–88 s). It is believed that Ca 2+ -sparks may underlie both the initiation and propagation of slow Ca 2+ -waves [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that close localization between SR and mitochondria may create functional interplay among them in limited microdomains with the exchange of Ca 2+ [ 32 , 33 , 34 ], providing rapid Ca 2+ buffering in mitochondria and limiting [Ca 2+ ] i [ 33 ]. As for pathophysiological relevance, it has been hypothesized that the interplay between SR and mitochondria may be involved in the induction of aberrant Ca 2+ -sparks, propagation of Ca 2+ -waves [ 29 ], and may increase the susceptibility for mPTP in the areas of close contacts of mitochondria with SR [ 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In their experiments, sparks were measured on the cells "at rest" but previously stimulated (1 Hz), and consequently the mechanisms underlying the release and recapture of calcium ions may be different (15,27).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ca 2+ spikes at the micro-molar range are commonly observed in the apical pole of pancreatic acinar cells to assist in limited exocytosis and secretion of zymogen granules in response to low IP 3 stimulation [ 60 , 61 ]. In cardiac myocytes, the opening of voltage-gated L-type Ca 2+ channels caused by membrane depolarization increases intracellular Ca 2+ level, triggering the opening of RyR2 and subsequent Ca 2+ sparks, an essential element in maintaining excitation-contraction coupling in healthy cardiac functions [ 62 ]. Moreover, Ca 2+ blips, also known as “triggering events” for Ca 2+ puffs, are formed by small, transient Ca 2+ elevations associated with the opening of a single IP 3 R channel.…”
Section: Er Ca 2+ -Releasing Channelsmentioning
confidence: 99%